Cognitive and moral development in assaultive and non-assaultive criminal : the case of Pakistan generalized and correction population - Tarique Muhammad Nizamani,; Novel Anak Lyndon, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article was undertaken in an attempt to integrate data from the realm of personality psychology with data of a more sociological nature. The main objective of the research was to explore differences between assaultive and non-assaultive criminals in the general areas of moral and cognitive development. In the study 38 males convicted of various offenses, both assaultive and non-assaultive, were administered a detailed demographics interview, and the processes they employ in the evaluation of self and others were assessed. T-tests were computed on the cognitive and moral development variables, and multiple regression was carried out with the cognitive and moral development variables. The results indicated that there is more involved in moral decision making than can be assessed by a simple pencil and paper technique, and demonstrated that logical reasoning skills are not a major area of difference between assaultive and non-assaultive criminals.